Why do they Keep Going Back? Exploring Women's Discursive Experiences of Intimate Partner Abuse - Hayes, Sharon; Jeffries, Samantha (International Journal of Criminology and Sociology, 2013)
Abstract: This paper explores how different discourses of intimate partner abuse (IPA) may impact women's decisions to stay or leave their partners. More specifically, we ask: 1) what narratives are available to and used by heterosexual and non-heterosexual female survivors of IPA to make sense of their experiences? 2) How might these narratives impact women's ability, or lack thereof, to disengage from their abusive partners? Prior literature suggests that there are four possible discourses on which women may draw including psychological (victim and offender), gendered political, and the narrative of romantic love. Analysis of discussion forums from online social networking sites revealed that while each of these discourses are utilised by women, scripts of romantic love may provide the strongest motivation for accepting and maintaining an abusive relationship. In contrast, understanding the psychological motivations of their abusers may empower female survivors to extricate themselves from the violence.